Three dimensional porous scaffolds derived from collagen, elastin and fibrin proteins orchestrate adipose tissue regeneration. (May 2021) - Sawadkar, Prasad; Mandakhbayar, Nandin; Patel, Kapil D; Buitrago, Jennifer Olmas; Kim, Tae Hyun; Rajasekar, Poojitha; Lali, Ferdinand; Kyriakidis, Christos; Rahmani, Benyamin; Mohanakrishnan, Jeviya; Dua, Rishbha; Greco, Karin; et al.
Current gold standard to treat soft tissue injuries caused by trauma and pathological condition are autografts and off the shelf fillers, but they have inherent weaknesses like donor site morbidity, immuno-compatibility and graft failure. To overcome these limitations, tissue-engineered polymers are seeded with stem cells to improve the potential to restore tissue function. However, their interaction with native tissue is poorly understood so far. To study these interactions and improve outcomes, we have fabricated scaffolds from natural polymers (collagen, fibrin and elastin) by custom-designed processes and their material properties such as surface morphology, swelling, wettability and chemical cross-linking ability were characterised. By using 3D scaffolds, we comprehensive assessed survival, proliferation and phenotype of adipose-derived stem cells in vitro. In vivo, scaffolds were seeded with adipose-derived stem cells and implanted in a rodent model, with X-ray microtomography, histology and immunohistochemistry as read-outs. Collagen-based materials showed higher cell adhesion and proliferation in vitro as well as higher adipogenic properties in vivo. In contrast, fibrin demonstrated poor cellular and adipogenesis properties but higher angiogenesis. Elastin formed the most porous scaffold, with cells displaying a non-aggregated morphology in vitro while in vivo elastin was the most degraded scaffold. These findings of how polymers present in the natural polymers mimicking ECM and seeded with stem cells affect adipogenesis in vitro and in vivo can open avenues to design 3D grafts for soft tissue repair.